(untitled) (Orfeu, 2021)
This article is a preliminary to a qualitative approach research that had Portuguese and Brazilian musicians as social subjects who became teachers. The work aims to discuss the path and processes by which they built their recognition as music teachers, based on narrative interviews and reflect on the potentialities of this strategy of telling stories of their life history in the investigation in the area of Music Education. The results, interpreted, reach a complex set of moments and events, drawing paths for some unexpected and unwanted, which as a whole provide experiences in which they perceive the sense of being in the relationship with the other. and in which they build the knowledge that they mobilize in their professional daily lives, allowing the "teaching knowledge" to escape the exclusivity of academic education, being also built through the constant displacement of the past and future of these social subjects.